Le Méridien de Greenwich de Jean Echenoz ou l’espace-temps romanesque - Macé, Marie-Anne (2018)
This paper analyses the stylistic relationship between Jean Echenoz’s novelistic writing, namely in Le Méridien de Greenwich, and Nouveau Roman writing. Some relevant continuity features will appear for the approach of contemporary French literature.